NARRATIVAS SOBRE O DIREITO À EDUCAÇÃO EM DISPUTA: luzes antropológicas para compreender as mobilizações juvenis - Valdeci Reis (Universidade Federal do Maranhão, 2019)
Ethnographic study, with a review of the literature on the social construction of the concept of youth, in order to report and analyze youth narratives around the right to education.The empirical analysis selected two waves of mobilizations carried out by young students: Acts in defense of public educational institutions occurred in the city of Florianópolis-SC, Brazil;In the capital of Argentina, Buenos Aires, the ethnographic narrative focused on the analysis of mobilizations carried out by young people who went to the streets demanding the maintenance of the “National Education Law”, as well as to stand radically against the austerity measures announced by the MaurícioMacri Government. The analysis of the ethnographic data indicates that the agenda in defense of education is capable of uniting collectives and organizations affiliated to the most diverse ideological currents.